2021
DOI: 10.3389/fpls.2021.636973
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genes and Genetic Loci Associated With Root Morphological Traits, Phosphorus-Acquisition Efficiency and Phosphorus-Use Efficiency in Chickpea

Abstract: Chickpea—the second most important grain legume worldwide—is cultivated mainly on marginal soils. Phosphorus (P) deficiency often restricts chickpea yields. Understanding the genetics of traits encoding P-acquisition efficiency and P-use efficiency will help develop strategies to reduce P-fertilizer application. A genome-wide association mapping approach was used to determine loci and genes associated with root architecture, root traits associated with P-acquisition efficiency and P-use efficiency, and any ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Technological advances in next-generation sequencing-based genotyping technologies have enabled GWAS to be used routinely in crop genetics research (Song et al 2016 ; Cao et al 2019 ). Several studies have demonstrated the efficiency of GWAS to identify marker-trait associations (MTAs) regulating important agronomic traits and to detect the underlying putative genes in different plant species such as Arabidopsis thaliana (Ren et al 2019 ), rice (Xu and Crouch 2008 ; Li et al 2014 ), maize (Yang and Zhu 2005 ), wheat (Wang et al 1999 ), cotton (Lai et al 2016 ), soybean (Hyten et al 2008 ; Cao et al 2017 ; Fang et al 2017 ; Li et al 2017 ; Chang et al 2018 ), chickpea (Varshney et al 2019a , b ; Thudi et al 2021 ), pigeonpea (Varshney et al 2017a , b ), and pearl millet (Varshney et al 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in next-generation sequencing-based genotyping technologies have enabled GWAS to be used routinely in crop genetics research (Song et al 2016 ; Cao et al 2019 ). Several studies have demonstrated the efficiency of GWAS to identify marker-trait associations (MTAs) regulating important agronomic traits and to detect the underlying putative genes in different plant species such as Arabidopsis thaliana (Ren et al 2019 ), rice (Xu and Crouch 2008 ; Li et al 2014 ), maize (Yang and Zhu 2005 ), wheat (Wang et al 1999 ), cotton (Lai et al 2016 ), soybean (Hyten et al 2008 ; Cao et al 2017 ; Fang et al 2017 ; Li et al 2017 ; Chang et al 2018 ), chickpea (Varshney et al 2019a , b ; Thudi et al 2021 ), pigeonpea (Varshney et al 2017a , b ), and pearl millet (Varshney et al 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating genome-wide sequence information with precise phenotypic variation has the potential to detect accessions with Huang and Han, 2014). Owing to its high resolution, cost effectiveness and non-essential pedigrees, association mapping has been able to dissect many important traits in chickpea, such as concentration of mineral nutrients (Diapari et al, 2014;Upadhyaya et al, 2016;Fayaz et al, 2022;Samineni et al, 2022); seed yield (Basu et al, 2018); drought tolerance (Li et al, 2018); root morphology, phosphorous acquisition, and use efficiency (Thudi et al, 2021); and salinity tolerance (Ahmed et al, 2021). The major challenge for GWAS is to control the false positives, primarily caused by population structure and family relatedness (Kaler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Population stratification has been established in the chickpea reference set ( Thudi et al, 2021 ), with three clusters/subpopulations independent of biological status and seed type. In the present study, we detected three subpopulations with ADMIXTURE in the reference set, including 258 accessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned reports, GWAS has also been conducted for yield and related traits in chickpea (Li et al, 2021), root morphological traits (Thudi et al, 2021), nutrient content (Diapari et al, 2014;Sab et al, 2020) and abiotic tolerance traits (Thudi et al, 2014;Samineni et al, 2022). Thus, the associated genomic regions identified through GWAS could be used for breeding programs to improve yield-related traits, nutrient content, and biotic and abiotic stress tolerance in chickpea.…”
Section: Genome-wide Association Studies For Broadening the Genetic B...mentioning
confidence: 99%